Blue Laws Matter: Post-Jim Crow Police Power, Stop and Frisk, and the Agents that Populated the Carceral State - Di Carlo, Jonathan Michael (Université d'Ottawa / University of Ottawa, 2023)
This thesis analyzes the legal history of the Supreme Court’s Fourth Amendment case law as it relates to the police practice of Stop and Frisk which shifted drastically in 1968 with the creation of the “Terry Stop”. From that decision, it analyzes the broader role that both the Judiciary and Law Enforcement, as fundamental American institutions, played in the creation of the Carceral State. This research draws on archival Supreme Court records to demonstrate that the decision to reinterpret the Fourth Amendment’s prohibition on warrantless searches and seizures was made in full view of the politicization and racialization of crime. Further, it shows that the Supreme Court both faced and succumbed to the immense pressure that Law Enforcement, lobbyists, and the United States Department of Justice placed on it. In response, the Court created a semantic carveout of the Fourth Amendment that permitted the practice of racially motivated Stop and Frisk, and the confiscation of contraband found during such frisks as evidence of a crime. In doing so, the Court demonstrated its allegiance to Law Enforcement—in the face of significant evidence to the contrary—by continually dismissing arguments that police practices were motivated by negative stereotypes. In legalizing the Stop and Frisk in 1968, the Court empowered Law Enforcement to practices to gradually shift away from the racially motivated police harassment from the Vagrancy Regime of the Jim Crow era to a constitutionally permissible Stop and Frisk regime. This thesis situates the advent of that change in Police Power which brought about this new regime as a primordial cornerstone in the creation of the Carceral State which was characterized by police as the agents who gathered Black bodies from American streets into the justice system.
Keywords: Carceral State; Stop and Frisk; Social History; Legal History; American History; Police Power; Constitutional Law; African American History; Civil Rights; Criminal Law